A Taxonomic Revision of Boas (Serpentes: Boidae) - Pyron, R. Alexander; Reynolds, R. Graham; Burbrink, Frank T. (Zootaxa, 2014)
Large molecular datasets including many species and loci have greatly improved our knowledge of snake phylogeny, particularly within the group including boas (Table 1). Recent taxonomic revisions using molecular phylogenies have clarified some of the previously contentious nomenclature of the group (Wilcox et al. 2002; Lawson et al. 2004; Burbrink 2005; Noonan & Chippindale 2006), resulting in a robust taxonomy that is mostly concordant with the phylogeny as currently known, which includes 85% of described, extant species (Pyron et al. 2013; Reynolds et al. 2014). However, a few unresolved issues remain, related primarily to the rules of the International Code of Zoological Nomenclature (the Code hereafter) and the application of Linnaean ranks (International Commission on Zoological Nomenclature et al. 1999).